Evaluation of different treatments to reduce the impact of Dothistroma septospora on three-year old Pinus radiata - Contreras, Rodolfo H. (Bosque (Valdivia), 1988)
To assess the efficiency of different treatments in reducing the effect of Dothistroma septospora on the growth of young Pinus radiata, six treatments and a control were defined. The treatments included fertilization, the use of herbicide or fungicide and a combination of both at plantation. For comparison, at plantation, two growth thresholds were treated annually with fungicide being one of them additionally treated with herbicide. The diameter growth proved to be more efficient than height to assess the efect of treatments. Fungicide applied after one years significantly reduce the disease intensity, but did not overcome the threshold growth. Herbicide at plantation and fungicide after one year, exceeded the control growth in 20%